Engaging with Environmental Issues as a Musician: Career Perspectives from the Musicians of the Playlist for the Planet. - Publicover, Jennifer L.; Duinker, Peter N.; Wright, Tarah S.; Baur, Steven (Popular Music & Society, 2019)
Education plays an essential role in tackling humanity's many environmental problems. Musicians, like other artists, may sometimes address environmental themes in their work. Whether or not they view themselves as such, they may at times act as environmental educators, communicators, and advocates through their art and other activities. We interviewed a cohort of musicians who engaged with environmental issues, both onstage and offstage, to uncover the parameters and impacts of this engagement on their lives in the music industry. Authenticity emerged as a prominent theme, as well as many perceived challenges, risks, mitigation strategies, and rewards associated with this work.